2021
DOI: 10.3126/ojn.v11i1.39040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Fear and Anxiety among Orthodontic patients visiting Nobel Medical College

Abstract: Introduction: Anxiety is the state of feeling nervous or worried that something bad is going to happen. Dental anxiety is defined as a patient’s response to stress that is associated with a dental procedure. The aim of our study is to investigate the anxiety status of dental patients visiting Orthodontic department at Nobel Medical College Teaching Hospital, Biratnagar. Materials and Method: Total 80 ongoing orthodontic patients (M =21 F=59) who completed modified Dental Anxiety Scale questionnaire were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study of orthodontic patients found that 65% had moderate anxiety, 25% had mild anxiety and 9% had severe to extreme anxiety. (ACHARYA et al 2021). The prevalence of dental anxiety in the New Zealand adult population was reported to be 13.3% (SUKUMARAN et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study of orthodontic patients found that 65% had moderate anxiety, 25% had mild anxiety and 9% had severe to extreme anxiety. (ACHARYA et al 2021). The prevalence of dental anxiety in the New Zealand adult population was reported to be 13.3% (SUKUMARAN et al 2020).…”
Section: Introductionmentioning
confidence: 99%